Performance of Lateral Loads Resisting Systems for Tall Steel Structure - Amit K. Mali, Hiral R. Luhar, Dipak N. Mali, Rajesh V. Sonagara, Snehal V. Mevada (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In modern age, as the construction of high-rise buildings and mega structures increases which decreases availability of land and increases land cost, to overcome that problems engineers have to go vertically by constructing tall structures. There are various lateral load resisting systems for tall structure, among them bracing systems, shear wall systems, outrigger systems and diagrid systems are selected for this work.For G+19 storied building, the structure is not provided with any lateral load resisting system then it is difficult to construct conventional structure. Parametric study and detailed comparison of various lateral load resisting system with respect to conventional structure was carried out for regular buildings. In this study bracing systems, shear wall systems, outrigger systems and diagrid systems are analyzed and designed. The study mainly focused on to determining the most effective and economical lateral load resisting system which can resist lateral forces effectively. Various parameters like maximum top lateral displacement, maximum base shear, Structure weight, maximum storey displacement and maximum storey drift are considered in this study. Bracing system was most economical and lighter structural system as compared to conventional systems and all other lateral load resisting systems.